"I Want to, But How?" Defining Counselor Broaching in Core Tenets and Debated Components. Issue 2 (6th April 2021) - King, Kelly M.
Abstract : Although counselor broaching of cultural identities and structural issues with clients is broadly supported by the counseling profession, how to do so most effectively has been debated. In this article, I identify core tenets, or commonalities, across the broaching literature and critically examine the debates about specific components of broaching practice. I define the term broaching and invite empirical tests of broaching components to begin a process of translating culturally responsive theory into an observable, evidence‐based skill set. A pesar de que en la práctica profesional de la consejería se aprueba mayoritariamente el abordamiento de las identidades culturales y problemas estructurales con los clientes, aún se debate cómo hacerlo de la forma más efectiva. En este artículo, identifico principios fundamentales, o rasgos comunes, en la literatura sobre el abordamiento y examino críticamente los debates sobre componentes específicos de la práctica del abordamiento. Defino el término abordamiento y solicito pruebas empíricas de los componentes del abordamiento para iniciar el proceso de convertir una teoría culturalmente sensible en un conjunto de habilidades observables y basadas en pruebas.